Mutagenicity studies with urine concentrates from coke plant workers. - Møller, Morten; Dybing, Erik (Scandinavian Journal of Work, Environment & Health, 1980)
Urine from coke plant workers, collected before and after work, were tested for the content of mutagenic substances in the Salmonella test system. Urine extracts from exposed smokers showed mutagenic activity, whereas urine from exposed nonsmokers did not. The mutagenicity of exposed smoker`s urine was not significantly different from that of urine from nonexposed smokers. Mutagenicity of smokers` urine was only evident in the presence of a rat liver metabolic activation system. The addition of beta-glucuronidase did not enhance the mutagenic effect. The facts that coke plant workers are exposed to very high levels of polycyclic aromatic hydrocarbons (PAH) and that there is no observed enhanced mutagenicity of their urine indicate that the mutagenicity observed with urine from smokers is not due to conventional PAH.
Keywords: Salmonella typhimurium; coke plant; coke plant worker; mutagene; mutagenicity; mutagenicity study; PAH; polycyclic aromatic hydrocarbon; urinary excretion; urine; urine concentrate